Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Cooperation between teachers and special educators is a central requirement for inclusive schools in which students both with and without special educational needs are taught together. In many studies the autonomy/equity norm is reported as a significant obstacle for cooperation. It implies that teachers strive towards a high amount of autonomy in the sense of ‘privacy in their classroom’ as a reaction to endemic uncertainties of pedagogical work and specific work conditions in schools. Nevertheless, some studies point out that general and special educators strive for and engage in intense forms of cooperation. In this study it is argued from a self-determination theory perspective that cooperation can be accompanied by high values of perceived autonomy if teachers internalized the need for cooperation as part of their professional identity. Furthermore, factors affecting the frequency of cooperation, perception of goal conflict frequency, and stress caused by goal conflicts relating to the endemic uncertainties of pedagogical work are investigated. Analyses were carried out using survey data collected from 222 general and special educators working in either inclusive primary schools, or special schools where pupils had specific special educational needs in the domain of ‘learning’. A key outcome of the study is the absence of the anticipated negative effect of cooperation on the perception of autonomy. This underlines doubts regarding the relevance of the autonomy/equity norm. In addition to that, having special educators with greater levels of experience, as well as the support of the principal through providing fixed time slots for cooperation are identified as central factors supporting cooperation in inclusive schools. Moreover, increased levels of cooperation were found to reduce the perception of goal conflict frequency and stress relating to goal conflicts for general educators. The results of the study are discussed with regard to theoretical implications,the professionalization of general and special educators and opportunities to enhance cooperation and supportive settings in inclusive schools. Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF

Inklusion im Bremer Schulsystem - Idel, Till-Sebastian; Lütje-Klose, Birgit; Grüter, Sandra; Mettin, Carlotta; Meyer, Andrea; Neumann, Phillip; Büttner, Gerhard; Hasselhorn, Marcus; Schneider, Wolfgang (Zweigliedrigkeit und Inklusion im empirischen Fokus. Ergebnisse der Evaluation der Bremer Schulreform)

Mittendrin oder nur dabei? Sonderpädagogischer Förderbedarf und soziale Partizipation - Neumann, Phillip (SCHULE inklusiv)
Keywords: Soziale Partizipation; Inklusion; Sonderpädagogik; Grundschule

Global generalized solutions to a parabolic-elliptic Keller-Segel system with singular sensitivity - Black, Tobias (Discrete & Continuous Dynamical Systems - S)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics; Analysis

The Stokes Limit in a Three-Dimensional Chemotaxis-Navier–Stokes System - Black, Tobias (Journal of Mathematical Fluid Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Condensed Matter Physics; Mathematical Physics

A Keller‐Segel‐fluid system with singular sensitivity: Generalized solutions - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Mathematical Methods in the Applied Sciences)
Keywords: General Engineering; General Mathematics

Stabilization in the Keller–Segel system with signal-dependent sensitivity - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Applicable Analysis)
Keywords: Applied Mathematics; Analysis

Émilie Du Châtelet zwischen Leibniz und Kant. Du Châtelet in der Eberhard-Kant-Kontroverse - Hagengruber, Ruth Edith (Emilie Du Châtelet und die deutsche Aufklärung)
In seiner Auseinandersetzung mit Immanuel Kant bestreitet Johann August Eberhard Kants Anspruch, in seiner Transzendentalphilosophie die Reichweite und Grenzen des Verstandes auf neue, zuvor nicht dagewesene Weise definiert zu haben. Eberhard dagegen meint die Prinzipien und Grundbegriffe transzendentalphilosophischer Erkenntniskritik schon aus der Leibniz-Wolffschen Schule ableiten zu können. An einschlägiger Stelle -- im dritten Teil seiner Ausführungen Über den wesentlichen Unterschied der Erkenntnis durch die Sinne und durch den Verstand -- belegt er diese Behauptung mit einem Verweis auf die {\glqq}Definition{\grqq} der Erscheinung in den Institutions physiques der Philosophin und Mathematikerin Du Châtelet.

Introduction - Hagengruber, Ruth Edith; Hutton, Sarah (British Journal for the History of Philosophy)

Primer - Diester, Michel (Filmische Moderne. 60 Fragmente)

Die sprechende Stadt. Stadtumbau in Paderborn um 1600 und in der Gegenwart - Süßmann, Johannes

Einführung - Eybl, Franz M.; Fulda, Daniel; Süßmann, Johannes (Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung)

Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung

Das Mainufer von Aschaffenburg: Romantische Geschichtsinszenierung und Herrschaftslegitimation - Süßmann, Johannes (Kolossale Miniaturen. Festschrift für Gerrit Walther)
Keywords: Aschaffenburg Ludwig I. König von Bayern Gartenkunst Main Residenzschloß Villen Gärtner; Friedrich von Antikenrezeption Museen Herrschaftslegitimation Bildungsbürger

Blow your Trumpets Gabriel« – Der Heavy Metal und die Frage des Satanismus - Hansen, Christin (Kirchliche Zeitgeschichte)

Vernünftige Deutsche, chaotische Griechen? Stereotype und historisches Lernen - Hansen, Christin; Pleitner, Berit (Geschichte lernen)

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

The full range of leadership. Welche Zusammenhänge gibt es zwischen Führungsverhalten und schulischen Qualitätsindikatoren? - Bloh, Bea; van Ophyusen, Stefanie (Schulmanagement)

Forschendes Lernen in der Lehrerausbildung – Gestaltung und Erforschung des Praxissemesters - Bloh, Bea; Behrmann, Lars; Homt, Martina; van Ophuysen, Stefanie (Herausforderung Kohärenz: Praxisphasen in der universitären Lehrerbildung. Bildungswissenschaftliche und fachdidaktische Perspektiven)

Aural Worldmaking: An Introduction - Mildorf, Jarmila (CounterText)

The Irrelevance of Relevance Theory for the Study of Generic Fiction - Mildorf, Jarmila (Style)

Can Sounds Narrate? Prosody in Sound Poetry Performance - Mildorf, Jarmila (CounterText)

Ressourcenorientiertes Schreiben. Tagebücher, Skizzen und Notate in der sozio-therapeutischen Praxis. Mit einem Exkurs zum Tagebuch der Trauer von Roland Barthes - Mildorf, Jarmila; Ketteler, Daniel (Jahrbuch Literatur und Medizin)

Why Poetry Matters: Defamiliarization and Perspective in Poetry - Mildorf, Jarmila (Lyrik und Medizin)

„Der Imperativ des Nassauerns, Durchmogelns und Absahnens“: Debatten um Steuermoral in der BRD Anfang der 1980er Jahren - Schönhärl, Korinna (Geschichte in Wissenschaft und Unterricht)

Geld zurück! Internationale Finanzkontrolle in Griechenland im 19. Jahrhundert und in der Gegenwart - Schönhärl, Korinna (Grenzüberschreitende institutionalisierte Zusammenarbeit von der Antike bis zur Gegenwart)

Die Steuermoral weltweit. Eine Artikelserie in der Frankfurter Allgemeinen Zeitung in den Jahren 1963/64 - Schönhärl, Korinna (Moderner Kapitalismus. Wirtschafts- und unternehmenshistorische Beiträge)

"I don't see why I would ever want to use it": Analyzing the Usability of Popular Smartphone Password Managers - Seiler-Hwang, Sunyoung; Arias Cabarcos, Patricia; Marín, Andrés; Almenáres, Florina; Díaz Sánchez, Daniel; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

Poster: Towards a Framework for Assessing Vulnerabilities of Brainwave Authentication Systems - Becker, Karen; Arias Cabarcos, Patricia; Habrich, Thilo; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

A Survey on Adaptive Authentication - Arias Cabarcos, Patricia; Krupitzer, Christian; Becker, Christian (ACM Comput. Surv.)

Narrating Selves and the Literary from the Bible to Social Media (Partial Answers)

Aural Worldmaking: Audionarratological Approaches to Sound and Narrative (CounterText)

Dance, Text and Philosophy in Gertrude Stein’s ‘One Dancing’ and Roger Scruton’s Perictione in Colophon - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Autobiography, the Literary and the Everyday in Paul Auster's 'Report from the Interior' - Mildorf, Jarmila (Partial Answers)

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Symmetry and motion primitives in model predictive control - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Worthmann, Karl (MCSS)

Implikationen der digitalen Transformation für die didaktische Arbeit des betrieblichen Ausbildungspersonals - Gössling, Bernd; Hagemeier, Daniel; Janssen, Elmar; Sloane, Peter F. E. (Jahrestagung der DGfE-Sektion Berufs- und Wirtschaftspädagogik)

Berufsbildung 4.0 als didaktische Herausforderung : zum Umgang von Lehrkräften an berufsbildenden Schulen mit digitalisierten Arbeitswelten - Gössling, Bernd; Hagemeier, Daniel; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

TLS/PKI Challenges and Certificate Pinning Techniques for IoT and M2M Secure Communications - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia; Simon Sherratt, R. (IEEE Commun. Surv. Tutorials)

DNS/DANE Collision-Based Distributed and Dynamic Authentication for Microservices in IoT - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia (Sensors)

Octave-Band Microwave Frequency Synthesizer Using Mode-Locked Laser as a Reference - Bahmanian, Meysam; Tiedau, Johannes; Silberhorn, Christine; Scheytt, Christoph (2019 International Topical Meeting on Microwave Photonics (MWP))
An octave-band voltage-controlled oscillator is phase-locked on the envelope of the pulse train from a mode-locked laser. The locking scheme employs a balanced Mach-Zehnder modulator with two photodiodes as a phase detector. The phase.locked loop has a loop bandwidth of approximately 1MHz and an in-band phase noise of approximately -135dBc/Hz at all frequencies. The integrated jitter from 1kHz to 100MHz is 21fs, 18.3fs and 13.8fs at 5.016GHz, 7.6GHz and 10.032GHz carrier frequencies, respectively. To the authors' knowledge, this is the best jitter performance reported for a PLL with MZM-based phase detection and the first reported PLL of this type featuring an octave-band frequency range.

Die Auswirkungen der Digitalisierung auf die Bedeutung beruflicher Qualifikation aus betrieblicher Sicht - Harteis, Christian; Goller, Michael; Fischer, Christoph (Beruf, Beruflichkeit, Employability)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Assessment of Flexibilisation Potential by Changing Energy Sources Using Monte Carlo Simulation - Dunkelberg, Heiko; Sondermann, Maximilian; Meschede, Henning; Hesselbach, Jens (Energies)
In the fight against anthropogenic climate change, the benefit of the integration of fluctuating renewable energies (wind and photovoltaics) into the electricity grid is a widely proved concept. At the same time, a fluctuating and decentralised supply of energy, especially at lower voltage levels, leads to a local discrepancy in the power balance between generation and consumption. A possible solution in connection with demand side management is the grid-oriented flexibilisation of energy demand. The present study shows how the use of an innovative hybrid-redundant high-temperature heat system (combined heat and power (CHP), power-to-heat system (PtH), gas boiler) can contribute to a flexibilisation of the electrical energy demand of plastics processing companies. In this context, the flexibilisation potential of a company is to be understood as the grid-related change of the energy supply through a change of the energy sources within the framework of the process heat supply. For this purpose, an omniscient control algorithm is developed that specifies the schedule of the individual system components. A sensitivity analysis is used to test the functionality of the control algorithm. Determination of the electrical flexibilisation potential is carried out via a comprehensive simulation study using Monte Carlo methods. For this purpose, the residual load curves of four characteristic distribution grids with a high share of renewable energies as well as heat load profiles of injection moulding machines are taken into consideration. A frequency distribution provides information on the electrical flexibilisation potential to be expected depending on the various combinations. The evaluation is carried out using a specially introduced logic, which identifies grid-relevant changes in the company's power consumption as flexibilisation potential based on a reference load curve. The results show that a reliable energy supply for production is possible despite flexibilisation. Depending on the grid under consideration, there are differences in the exploitation of the potential, which essentially depends on the installed renewable capacity. Depending on the scenario under consideration, an average of up to 1486 kWhel can be shifted in a positive direction and 1199 kWhel in a negative direction.

On the impact of probabilistic weather data on the economically optimal design of renewable energy systems – a case study on La Gomera island - Meschede, Henning; Hesselbach, Jens; Child, Michael; Breyer, Christian (International Journal of Sustainable Energy Planning and Management)
Renewable energy and storage systems are widely discussed to minimise the impact of global warming. In addition to the temporal resolution of simulation tools, also the chosen input data might have a strong impact on the performance of renewable energy systems, and energy storage systems in particular. This study analyses the impact of probabilistic weather data on the design of renewable energy systems. The main objective is hereby the determination of the robustness of a recently state-of-the-art design process of a 100% renewable energy and storage system with varying probabilistic input data. The island of La Gomera, Canary Islands, is taken as a case study. Although all analysed systems show some variance in their results, the combination of vehicle-to-grid and power-to-hydrogen shows the best economic performance. Hereby, small island energy systems depending heavily on wind energy show higher variations than those with high shares of solar energy. This analysis illustrates clearly that the choice of one historical reference year is not suitable to determine the expected performance of an energy system. To learn about their sensitivity, synthetic probabilistic inputs as applied in this study are a good way to determine both the expected mean values and their variance.

Classification and clustering of the German plastic industry with a special focus on the implementation of low and high temperature waste heat - Dunkelberg, Heiko; Schlosser, Florian; Veitengruber, Frank; Meschede, Henning; Heidrich, Tobias (Journal of Cleaner Production)

On the transferability of smart energy systems on off-grid islands using cluster analysis – A case study for the Philippine archipelago - Meschede, Henning; Esparcia, Eugene A.; Holzapfel, Peter; Bertheau, Paul; Ang, Rosario C.; Blanco, Ariel C.; Ocon, Joey D. (Applied Energy)

Automatic Time Series Segmentation as the Basis for Unsupervised, Non-Intrusive Load Monitoring of Machine Tools - Seevers, J-P.; Johst, J.; Weiß, T.; Meschede, Henning; Hesselbach, J. (Procedia CIRP)